1999
DOI: 10.1111/j.1540-5915.1999.tb01621.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling IS Planning Benefits Using ACE

Abstract: This paper addresses the dearth of research on the determinants of IS planning benefits. Data were collected using a questionnaire survey of top IS executives from 450 companies in Singapore. Of the 103 responses (representing a response rate of 23%), 65 companies undertook IS planning. To test the hypothesis that the determinant-benefit relationships are likely to be nonlinear, the Alternating Conditional Expectations (ACE) algorithm was used. This appears to be the first use of ACE in IS planning research. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…SISP is thus intended to help the organization reach its goal of improved competitiveness, operations, and resource management [1,13].…”
Section: The Sisp Processmentioning
confidence: 99%
“…SISP is thus intended to help the organization reach its goal of improved competitiveness, operations, and resource management [1,13].…”
Section: The Sisp Processmentioning
confidence: 99%
“…27 McFarlan et al 28 assert that the standing and role of information systems within different types of businesses positively contribute to business strategies, while the strategic role of the information system varies in accordance with top managers' participation and planning. Ang et al 29 point out that top managers must provide sufficient resources and assist in the planning of the information systems to facilitate its success within the organization. Moreover, McDonough 30 identifies that the support of top managers on project teams will have a direct impact on adoption success.…”
Section: Assimilation Level After the Introduction Of Information Sysmentioning
confidence: 99%
“…As responses from management and frontline staff were separated for analysis, we had a total of 40 independent variables. A factor analysis was conducted to reduce the number of variables to a parsimonious and smaller set before ACE analysis (Ang et al, 1999;Hays & Hill, 2001ab;Sum et al, 1995). Several tests were conducted on the suitability of the data for factor analysis (Hair et al, 1998;Hays & Hill, 2001ab).…”
Section: Improvement (Frontline)mentioning
confidence: 99%
“…However, related literature on learning and motivation has suggested that employee variables affect performance in a non-linear fashion. For example, learning is non-linear (Ang, Quek, Teo, & Liu, 1999;Argote, Beckman, & Epple, 1990;Baloff, 1971;Givons & Horsky, 1990;Little, 1979;Yelle, 1979). Similarly, the literature on motivation has also suggested non-linear performance-motivation relationships where performance first increases with motivation but then could decrease at high levels of motivation (Birch, 1945;McClelland, 195 1;Patrick, 1934;Vroom, 1964;Yerkes & Dodson, 1908).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation